Exploring Gender Differences in Students’ Perceptions of STEM Careers, Systems Thinking Skills, and Environmental Literacy - Oktavia, Indri; Shidiq, Ari Syahidul; Yamtinah, Sri; Putri, Putu Anindita Widya (Vidya Karya, 2026)
STEM-based learning plays an important role in preparing students to face the challenges of the 21st century, particularly in developing systems thinking skills, environmental literacy, and career orientation in science and technology fields. Indonesia's performance in international assessments such as PISA and TIMSS, which remains below the global average, indicates the need to strengthen STEM education in schools. This study aims to analyze high school students' perceptions of STEM careers, systems thinking abilities, and environmental literacy in the context of chemistry learning. A quantitative descriptive method was used in this research, involving 101 high school students, consisting of 28 males and 73 females. Data were analyzed using descriptive statistics in the form of frequencies and percentages. Overall findings indicate that students have positive perceptions of the three variables studied. However, the ability to formulate solutions to complex chemistry problems and confidence in solving environmental issues still need improvement. For future research, it is recommended to develop more contextual STEM-based learning models to further strengthen students' systems thinking skills and environmental literacy.